Geographic dispersion of invasive crop pests: the role of basal, plastic climate stress tolerance and other complementary traits in the tropics - Nyamukondiwa, Casper; Machekano, Honest; Chidawanyika, Frank; Mutamiswa, Reyard; Ma, Gang; Ma, Chu-Sen (Elsevier, 2022)
Global pest invasions have significantly increased in recent years. These invasions together with climate warming directly impact agriculture. Tropical climates feature extreme weather events, including high temperatures and seasonal droughts. Thus, successful invasive pests in tropics have to adapt to these extreme climate features. The intrinsic factors relevant to tropical invasion of insects have been explored in many studies, but the knowledge is rather dispersed in contemporary literature. Here, we reviewed the potential biophysical characters of successful invasive pests’ adaption to tropical environments including [1] inherent high basal stress tolerance and advanced life-history performances [2], phenotypic plasticity [3], rapid evolution to environmental stress, polyphagy, diverse reproductive strategies and high fecundity. We summarised how these traits and their interactive effects enhance pest invasions in the tropics. Comprehensive understanding of how these characters facilitate invasion improves models for predicting ecological consequences of climate change on invasive pest species for improved pest management.